SELF-DIRECTED LEARNING SEBAGAI MODEL BELAJAR PESERTA DIDIK HOMESCHOOLING TAMAN SEKAR BANDUNG - SYAUQI FAJAR RUKMANA, - (2021)
ABSTRACT SELF-DIRECTED LEARNING AS A STUDENT LEARNING MODEL IN HOMESCHOOLING PARK OF SEKAR BANDUNG Syauqi Fajar Rukmana Nim. 1505344 Homeschooling is one way of completing an education program that is carried out informally, one of the learning models developed in homeschooling is Self-Directed Learning. This study aims to obtain a description of the needs of prospective students themselves. In obtaining maximum value in the learning process, Homeschooling Taman Sekar Bandung applies Self-Directed Learning as a learning model for students to obtain maximum scores. Therefore, the learning process is carried out with Self-Directed Learning. The purpose of this study is to obtain an overview of the role of managers in implementing Self-Directed Learning, the Self-Directed Learning process, and the obstacles faced by students who use the Self-Directed Learning model. This study uses a descriptive method with a qualitative approach to Homeschooling Taman Sekar Bandung. The data were collected using data collection techniques by interview, observation, and documentation study. The research subjects were twelve people, one homeschooling manager, two homeschooling tutors, three parents of homeschooling students and six homeschooling students. Research finds that; 1) There are six stages carried out by the manager in implementing Self-directed Learning, namely setting the learning atmosphere, identifying learning needs, formulating learning objectives, identifying learning abilities and learning resources, implementing and selecting strategies in learning, evaluating learning outcomes. 2) The learning process using the Self-Directed Learning model requires students to organize themselves independently both in achieving competencies and choosing ways to achieve these competencies. There are four processes in the self-directed learning model, that is planning, implementing, monitoring and evaluating. 3) There are two obstacles for students who use the Self-Directed Learning model, that is intrinsic and extrinsic, intrinsic barriers are the lack of motivation stability of students in learning activities, while extrinsic obstacles are other activities that interfere with learning activities. Keywords: Self-Directed Learning, Homeschooling, Students